Tinjauan Etika Bisnis Islam pada Praktik Konsinyasi - Agvina Rachmayanti; Nanik Eprianti (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Islamic business ethics is the study of what is good or bad, right or wrong in the world of commerce or business based on the principle of morality. There are 7 axioms of Islamic business ethics, namely Falah, Mashlahat, Unity,Equilibrium, Free Will, Responsibility, Benevolence. In carrying out the practice of consignment, the Divers Collective does not fulfill the 3 axioms of Islamic business ethics, namely the axioms of Equilibrium ,Responsibility and Free Will.The problem in this research is formulated ad follows: (1) How is the cooperation agreement made by Divers Collective?(2) How do you review Islamic business ethics on consignment practices at Divers Collective? This research uses the type of qualitative research with case study techniques. Interview, Observation and Documentation is a way of collecting data that aims to find out all the information to be analyzed by means of deductive analysis and conclusions drawn. Based on the results of the research that in terms of the agreement, the consignor is in default and is not in accordance with the axiom of Responsibility. In terms of marketing, the consignor has fulfilled the axiom of Benevolence business ethics. Meanwhile, in terms of sales, the consignor has not carried out the axiom of business ethics perfectly, namely regarding Free Will. Abstrak. Etika bisnis Islam adalah ilmu yang mempelajari tentang apa yang baik atau buruk, benar atau salah dalam dunia perdagangan atau bisnis didasari dengan prinsip moralitas. Ada 7 aksioma etika bisnis Islam, yaitu Falah, Mashlahat, Unity(Persatuan), Equilibrium(Keseimbangan), Free Will(Kehendak Bebas), Responsibility(Tanggung Jawab), Benevolence(Ihsan). Dalam melakukan praktik konsinyasi, pihak Divers Collective tidak memenuhi 3 aksioma etika bisnis islam yaitu aksioma Equilibrium (Keadilan), Responsibility (Tanggung Jawab) dan Free Will (Kehendak Bebas). Rumusan masalah dalam penelitian ini adalah : (1) Bagaimana perjanjian kerjasama yang dilakukan Divers Collective? (2) Bagaimana tinjauan etika bisnis Islam pada praktik konsinyasi di Divers Collective? Penelitian ini menggunakan jeni penelitian kualitatif dengan Teknik studi kasus. Wawancara, Observasi dan Dokumentasi merupakan cara pengumpulan data yang bertujuan untuk mengetahui segala informasi untuk dianalisis dengan alat analisis deduktif dan ditarik kesimpulan. Berdasarkan hasil penelitian bahwa dari segi perjanjiannya, pihak consignor melakukan wanprestasi dan tidak sesuai dengan aksioma Responsibility(Tanggung jawab). Dalam segi pemasaran, pihak consignor telah memenuhi aksioma etika bisnis Benevolence(Ihsan). Sedangkan dari segi penjualan, pihak consignor belum melakukan aksioma etika bisnis dengan sempurna yaitu mengenai Free Will(Kehendak Bebas).